Epidemiology of overuse injuries in youth team sports: A 3-year prospective study - Leppänen, M.; Pasanen, K.; Kannus, P.; Vasankari, T.; Kujala, U. M.; Heinonen, A.; Parkkari, J. (International Journal of Sports Medicine, 2017)
Prospective studies on overuse injuries and their impact on athletic training among youth team sports are scarce. The purpose of this study was to investigate the incidence, severity and player related risk factors of overuse injuries among young (12-20 years) basketball and floorball players. A total of 387 players participated in a 3-year prospective study. Each player completed a baseline questionnaire regarding their background information. Overuse injuries that prevented players to fully or partly participate in their regular training were collected. In all, 204 overuse injuries were registered (injury incidence 1.51 injuries/1 000 h of exposure; 95% CI 1.35-1.78). Most of the injuries involved the knee (35%) and lower back (21%), and were classified as severe (44%). Injury incidence was 1.51 (95% CI 1.2-1.82) and 1.61 (95% CI 1.32-1.91) in basketball and floorball, respectively. Incidence was significantly higher among female compared with male players (incidence rate ratio 1.58; 95% CI 1.20-2.09). Previous injury and playing at adult level were the strongest factors associated with occurrence of an overuse injury. In conclusion, overuse injuries of the knee and low back are relatively common in youth basketball and floorball. Effective prevention strategies as well as training load monitoring is needed in youth team sports.